Comparison of perceived educational value of an in-person versus virtual medical conference - Chan, Alex; Cao, Andrew; Kim, Leanne; Gui, Shannon; Ahuja, Manan; Kamhawy, Rana; Latchupatula, Lekhini (Canadian Medical Education Journal, 2021)
Purpose: Though prior literature has shown that virtual conferences improve accessibility and provide a comparable educational experience, further research is required to characterize their educational value. Methods: In this repeated cross-sectional study, demographic and survey data were compared between attendance perspectives for the in-person student-led internal medicine conference held in 2019 and subsequent virtual conference held in 2020. Results: There were 146 attendees at the in-person conference and 200 attendees at the online conference, in which 32 (22% response rate) and 52 responses (26% response rate) were gathered, respectively. Comparison of Likert Scale data via Mann-Whitney U Test revealed that learning objectives were better met in-person for the overall conference (p < 0.01) and didactic sessions (p < .05), but not for workshops, in which there was no significant difference. Survey takers noted the virtual conference to be more accessible on multiple factors, but felt as though their potential for interaction with other participants was more limited. Conclusions: Results indicate that though the virtual conference appeared more accessible to attendees, overall learning objectives for the conference and didactic sessions were better met in-person. Interestingly however, there was no observed difference in perceived educational value for small group workshops.